Diskursus Urgensi Carbon Emission Disclosure pada Perusahaan-perusahaan Publik di Indonesia - Umi Hanifah; W. Wahyono (Jurnal Penelitian, 2018)
This article explores the implementation and importance of carbon emission disclosure by public companies in Indonesia. The study is conducted by reviewed related literatures and previous research as references.  The study concludes that public companies in Indonesia have already disclosed carbon emission in their financial statements. However, the disclosure has not conducted in optimal manner. Those indicate that there are some actions already taken by them to response the global climate changes, especially the information about climate changes in Indonesia. Disclosure on carbon emission by public companies in Indonesia had positive impacts on the companies image.